Clinical diagnosis and treatment of subungual exostosis in children - Hao Li; Haichong Li; Xinyu Qi; Dong Guo; Jun Cao; Yunsong Bai; Ziming Yao; Xuejun Zhang (Frontiers Media S.A., 2022)
ObjectiveTo analyze and summarize the clinical characteristics and treatment effects for subungual exostosis in children.MethodsClinical data for children with subungual exostosis treated in our department from January 2008 to September 2022 were evaluated.ResultsForty children with subungual exostosis were evaluated, comprising 31 boys (77.5%) and 9 girls (22.5%) with a median age of 9 years (4-17 years). The median disease course was 6 months (1-48 months). Seven patients (17.5%) had definite trauma history and 5 (12.5%) had infection. The toe or finger nail appearance was abnormal in 36 patients and normal in 4 patients. Twenty-seven patients (67.5%) had pain when wearing shoes and walking, and 25 (62.5%) had toenail tenderness. The lesions were located in the distal phalanxes of the toes in 37 patients (92.5%), with 14 patients affected on the left side and 23 on the right side. Twenty-two patients had lesions in the great toe, 6 in the second toe, 6 in the third toe, and 3 in the fourth toe. The lesions in the other 3 patients (7.5%) were located in the distal phalanxes of the fingers, with 2 patients affected in the second finger and 1 in the third finger. Regarding the relationship between lesion location and nail bed, 4 patients were type I, 21 were type II, and 15 were type III. All 40 patients received surgical treatment, with nail removal in 15. The median maximum lesion diameter was 1.0 cm (0.8-2 cm), median operation time was 25 min (20-45 min), median blood loss was 1 ml (1-2 ml), and median postoperative hospital stay was 2 days (1-4 days). All cases were histopathologically confirmed as subungual exostosis. The median follow-up time was 24 months (3-60 months), with normal appearance of the toe or finger nail. There were no complications in 38 patients (95.0%). Two patients (5.0%) relapsed at 3 months postoperatively and underwent a secondary operation, with no subsequent recurrence during 12 months of follow-up.ConclusionSubungual exostosis in children is a rare benign disease that often occurs in the toes. Selection of the appropriate incision and nail bed treatment based on the relationship between lesion location and nail bed is helpful for improving the treatment effect.